Using Podcast Media on Teaching Listening in New Normal Era - Nenna Firmi Fatika; Endang Mastuti Rahayu (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2021)
The objective of this study was to describe the application of using podcast media on the teaching listening. The students did not interest and experience difficulty while learning listening because the media of listening was too monotonous and lack of innovation. Podcast is a combination of two words namely "iPod" (the name of a brand) and broadcast. This is a medium in the form of sound or video that can be accessed and followed via internet. This study used qualitative appoarch. The subject of this study was the 10th grade students on X sosbas 1(b) class of Antartika Sidoarjo Senior High School with total 15 students. In this study, researcher used participant observation, questionnaire and interview as a data collection techniques. The data of this study analyzed using data reduction, data display and conclusion drawing. Based on the result of participant observation, questionnaire and interview, it can be seen that the use of podcast in learning listening made the students easier to understand the material and the students felt happy and comfort while learning listening.Keywords: Podcast, teaching listening, new normal era